2018
DOI: 10.1159/000488625
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Kinase Inhibitor CZ415 Inhibits Human Papillary Thyroid Carcinoma Cell Growth

Abstract: Background/Aim: Mammalian target of rapamycin (mTOR) plays an important role in papillary thyroid carcinoma (PTC) cell progression. CZ415 is a novel, highly-efficient and specific mTOR kinase inhibitor. The current study tested the potential anti-tumor activity of CZ415 in human PTC cells. Methods: The established (TPC-1 cell line) and primary human PTC cells were treated with CZ415. Cell survival and growth were tested by Cell Counting Kit-8 assay and BrdU ELISA assay, respectively. Cell apoptosis was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 46 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…In thyroid carcinomas, inhibition of autophagy by Beclin 1 siRNA or 3-MA increased the sensitivity of TPC-1 cells to CZ415. 123 …”
Section: Beclin 1 and Head And Neck Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…In thyroid carcinomas, inhibition of autophagy by Beclin 1 siRNA or 3-MA increased the sensitivity of TPC-1 cells to CZ415. 123 …”
Section: Beclin 1 and Head And Neck Cancersmentioning
confidence: 99%
“…In thyroid carcinomas, inhibition of autophagy by Beclin 1 siRNA or 3-MA increased the sensitivity of TPC-1 cells to CZ415. 123 Inhibition of Beclin 1 may increase the antitumor effect obtained by suppressing long non-coding RNA (lncRNA). The lncRNA HOX transcript antisense RNA (lncRNA HOTAIR), which is localized in the endonuclear region, is a functional RNA molecule that contains more than 200 nucleotides and is upregulated in many cancers.…”
Section: Beclin 1 Is Associated With Treatment Resistancementioning
confidence: 99%
“…However, whether H 2 S is involved in the growth of human thyroid carcinoma cells remains unknown. Human thyroid carcinoma cell lines TPC-1, TT, and ARO cells have been widely implicated in establishing tumor-bearing animal models [4446]. In this study, TPC-1, TT, and ARO cells were used to evaluate the effects of exogenous H 2 S both in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…TPC-1, TT, and ARO cells have been widely adopted to establish subcutaneous xenograft models [4446]. We therefore examined the effect of exogenous H 2 S on the growth of human thyroid carcinoma xenograft tumors in BALB/c nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…20 TC is a major health threat to human beings all over the world. 21 Meanwhile, a new study has showed the influence of lncRNA TNRC6C-AS1 on proliferation, apoptosis and invasion of papillary TC cells. 8 In this study, we explored the role of the lncRNA TNRC6C-AS1, STK4…”
Section: Discussionmentioning
confidence: 99%